MILO Mobile: An iPad App to Measure Search Performance in Multi-Target Sequences. (June 2020) - Thornton, Ian M.; Horowitz, Todd S.
This article introduces a mobile app version of the Multi-Item Localization (MILO) task. The MILO task was designed to explore the temporal context of search through a sequence and has proven useful in both basic and applied research settings. Here, we describe the basic features of the app and how it can be obtained, installed, and modified. We also provide example data files and present two new sets of empirical data to verify that previous findings concerning prospective planning and retrospective memory (i.e., inhibitory tagging) are reproducible with the app. We conclude by discussing ongoing studies and future modifications that illustrate the flexibility and potential of the MILO Mobile app.